Professional cooking - Gisslen, Wayne (John Wliey & Sons, Inc., 2015)
Professional Cooking, Eighth Edition reflects the changing nature of our understanding of cooking and related fields such as food safety, nutrition, and dietary practices, as well as new thinking about how best to teach this material. Familiar material reflects the core curriculum that has stayed focused on the essentials, the comprehensive understanding of ingredients and basic cooking techniques that are the foundation of success in the kitchen.